Penegakan Hukum Terhadap Juru Parkir Tidak Resmi Di Kota Ambon - Oszaer, Rex Joshua; Nendissa, Renny Heronia; Tita, Heillen Martha Yosephine (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
Parking is a public need that initially functions to serve, according to this function parking space is adjusted according to demand along with the needs of people who have motorized vehicles to access a place. The purpose of this study was to analyze and find out the form of supervision carried out by the Ambon City Government towards unofficial parking attendants, as well as the implementation of law enforcement against unofficial parking attendants based on Ambon City Regional Regulation No. 6 of 2019. This research is normative juridical research, the process of finding legal principles and doctrines to answer legal issues that are systematically compiled, studied, then conclusions drawn, using statutory approach (statue approach) and conceptual approach (conceptual approach). The results of this research are that the Ambon City Government carries out internal supervision, a-priori and a-posteriori supervision in the form of preventive supervision in the form of appeals to the public, this supervision is carried out for approximately 2 years and then an evaluation is carried out. Law enforcement carried out by the Ambon City Government against managers and unofficial parking attendants in Ambon City as stipulated in CHAPTER XIII Concerning Administrative Sanctions Article 46, Article 47, and Article 48 paragraph (3).